2011
DOI: 10.1038/oby.2010.203
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Consuming Frequent, Higher Protein Meals on Appetite and Satiety During Weight Loss in Overweight/Obese Men

Abstract: The purpose of this study was to determine the effects of dietary protein and eating frequency on perceived appetite and satiety during weight loss. A total of 27 overweight/obese men (age 47 ± 3 years; BMI 31.5 ± 0.7 kg/m2) were randomized to groups that consumed an energy-restriction diet (i.e., 750 kcal/day below daily energy need) as either higher protein (HP, 25% of energy as protein, n = 14) or normal protein (NP, 14% of energy as protein, n = 13) for 12 weeks. Beginning on week 7, the participants consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 34 publications
2
50
0
2
Order By: Relevance
“…This response is not universal as another study demonstrated that liquid HP preloads did not alter satiety or energy intake differently compared with a liquid HC preload (28). In the context of chronic caloric restriction, studies have shown that a HP diet consisting of solid food is associated with greater satiation compared with a lower protein diet (12,13,14). Our data with liquid meals do not support these previous studies and show that during acute caloric restriction, liquid HP meals do not increase perceived fullness or reduce perceived hunger more than liquid HC meals over the course of an entire day of eating.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This response is not universal as another study demonstrated that liquid HP preloads did not alter satiety or energy intake differently compared with a liquid HC preload (28). In the context of chronic caloric restriction, studies have shown that a HP diet consisting of solid food is associated with greater satiation compared with a lower protein diet (12,13,14). Our data with liquid meals do not support these previous studies and show that during acute caloric restriction, liquid HP meals do not increase perceived fullness or reduce perceived hunger more than liquid HC meals over the course of an entire day of eating.…”
Section: Discussionmentioning
confidence: 93%
“…However, altering the composition of the diet may be helpful. Although limited, some studies suggest that chronic higher protein (HP) low-calorie diets (protein content 25-34% of energy) containing conventional solid foods increase perceived satiety more than lower protein, higher carbohydrate (HC) diets (protein content 14-18% energy) during weight loss in overweight and obese individuals (12,13,14). The increased satiety associated with HP meals during caloric restriction and weight loss may be because protein causes the greatest stimulation of postprandial PP (15) and PYY (16) secretion.…”
Section: Introductionmentioning
confidence: 99%
“…Ghrelin release increases in relation to the time since last feeding and has been shown to interact with receptors in the hypothalamus where it stimulates feeding behavior (Wren et al, 2000). During CR levels of ghrelin are increased (Barazzoni et al, 2003;Yang et al, 2007;Kinzig et al, 2009;Abou Heif et al, 2010;Gonzalez et al, 2008;Reimer et al, 2010;Leidy et al, 2011) relative to AL fed controls, and the levels rise in relation to the time on restriction for at least 4 weeks. However, not all studies report such an increase (Martin et al, 2007a).…”
Section: Ghrelinmentioning
confidence: 95%
“…In older adults, the outwardly paradoxical increase in the incidence of sarcopenic obesity highlights the need to look beyond the quantity of protein and energy consumed daily (16-18). Recent research efforts have clearly established the benefits of increased dietary protein within an energy controlled diet for weight management (16, 19). However, relatively few studies have examined issues such as protein distribution (20-22), or adopted an integrated approach to examine the concomitant effects of increased protein on a broad, cross-disciplinary array of outcomes/themes such as: protein metabolism, cell signaling, body composition, satiety, glucose regulation, and overall macronutrient consumption.…”
Section: Sarcopenia and Protein Recommendationsmentioning
confidence: 99%
“…We previously examined whether 6 small meals (i.e., 350 kcal/meal) consumed every 2 h improves daily appetite and satiety responses compared to the standard 3 larger meals (i.e., 700 kcal/meal) (45, 46). Protein quantity was also varied within each meal pattern.…”
Section: Timing and Distribution Of Consumptionmentioning
confidence: 99%